Clinical characteristics and treatment outcomes of parathyroid carcinoma: A retrospective review of 234 cases - Wang, Peisong (Oncol Lett, 2017)
Parathyroid carcinoma (PC) is one of the rarest known types of cancer and has a moderate prognosis, with estimated 5- and 10-year overall survival rates between 78–85% and between 49–70%, respectively. To raise awareness of this disease, and to optimize its diagnosis, clinical management and prognosis, the present study retrospectively reviewed 234 cases of PC. A total of 226 cases of PC, which were archived between 1984 and 2015 in the three major databases of the Chinese population, were retrieved and pooled with the 8 cases diagnosed and treated at the Department of Thyroid Surgery of The First Hospital of Jilin University (Changchun, China) between June 2008 and December 2015. The clinicopathological features, diagnosis, surgical procedures and outcomes of these cases of PC were investigated. The review revealed that misdiagnosis has been a considerable issue, with >80% of the patients misdiagnosed prior to surgery, and the accuracy of intraoperative diagnosis based on frozen sections was only 15.04%. The use of radical resection as first-line therapy significantly improved the disease-free survival by ~8 years (log-rank, 20.956; P<0.001); and, at relapse, reoperation prolonged patient survival by ~7 years (log-rank, 35.322; P<0.001). Consistently, a Cox proportional hazards analysis indicated that radical resection as a first-line therapy reduced the risk of postoperative recurrence (P=0.030), and that reoperation following recurrence significantly improved patient survival (P=0.030). The 5- and 10-year cumulative disease-specific survival rates of the cases of PC were 83 and 67%, respectively. Notably, an increased mortality rate was observed among males with PC compared with female patients with PC. In summary, in the past 32 years (1984–2015), the majority of patients with PC have been misdiagnosed. Performing radical resection as the first-line therapy significantly reduces recurrence and improves patient survival time; and, following relapse, subsequent surgery has also been demonstrated to be an effective approach.